Quality of Protection Evaluation of Security Mechanisms. (17th July 2014) - Ksiezopolski, Bogdan; Zurek, Tomasz; Mokkas, Michail
Abstract : Recent research indicates that during the design of teleinformatic system the tradeoff between the systems performance and the system protection should be made. The traditional approach assumes that the best way is to apply the strongest possible security measures. Unfortunately, the overestimation of security measures can lead to the unreasonable increase of system load. This is especially important in multimedia systems where the performance has critical character. In many cases determination of the required level of protection and adjustment of some security measures to these requirements increase system efficiency. Such an approach is achieved by means of the quality of protection models where the security measures are evaluated according to their influence on the system security. In the paper, we propose a model for QoP evaluation of security mechanisms. Owing to this model, one can quantify the influence of particular security mechanisms on ensuring security attributes. The methodology of our model preparation is described and based on it the case study analysis is presented. We support our method by the tool where the models can be defined and QoP evaluation can be performed. Finally, we have modelled TLS cryptographic protocol and presented the QoP security mechanisms evaluation for the selected versions of this protocol.